Influence Teacher Professionalism Towards Motivation Learning and Ability Think Critical Students in Social Studies Learning Class V SD Inpres 1 Kayumalue Tax - Ika Citra Pratiwi; Lukman; Misnah (Kirana Publisher (KNPub), 2024)
Education is all something that affects growth , change and conditions every human . The changes that happen is development potential child educate , good knowledge , skills , and attitude in his life . Ability think critical student refers to the ability For analyze , evaluate , and interpret information, ideas or problem with objective way . Formulation​ problem study How influence teacher professionalism towards motivation learning and ability think critical students in social studies learning . Research objectives This is to (1) test and find out influence teacher professionalism towards motivation learning and ability think critical students . The sample used as many as 30 students Class V of SD Inpres 1 Kayumalue Pajeko . Research This is study quantitative . The data used in study This using primary data obtained from answer Respondent on questionnaire / questions . Data analysis using the Statistical Package for the Social Sciences (SPSS) for Windows version 25 with Independent Samples Test technique . Research results This show that (1) teacher professionalism has an influence to motivation Study students , because mark ???????????? ≥ 0.005, namely 0.092. (2) teacher professionalism has an effect to ability think critical students , grades ???????????? ≥ 0.005 which is 0.089.